A review of the book: managerial uses of accounting information by Joel S. Demski / BChoirunnisa Arifa and Sardar M. N. Islam - Arifa, BChoirunnisa; M. N. Islam, Sardar (Faculty of Accountancy, 2013)
Joel Demski’s book is an excellent book in accounting that provides an insightful and comprehensive study on managerial accounting using issues through a new approach based on economic theory and quantitative methods.